(untitled) (International Journal of Engineering and Computer Science, 2013)
Today’s transport system has evolved from horse driven carriages and paved roads to a more complex road transport system made up of a variety of vehicles and other infrastructure, all put in place in order to support safe and efficient mobility of vehicles. The next step to further improve the transportation system of today is to make the vehicles and roadside infrastructure more intelligent by making them communicates with each other. This new ability will help find new solutions to current problems like traffic congestion, vehicle accident, monitoring of adherence to traffic rules and alerting the responsible authorities of any traffic rule violation or accident for immediate management. Speed limit violation and inefficiency accident information dissemination in public road transport are recognized as one of the causes leading to traffic accidents and the failure of emergency Medical Services personnel to reach the victim during the socalled “Golden Hour” after the accident in Tanzania. This paper surveys the current system being used for speed management and Accident Reporting management in Tanzania. It also suggests recommendations for the implementation of systems that will effectively influence driving speeds and accident reporting management thereby significantly increase public transport safety